Analisis Laju Sedimentasi Pada Saluran Irigasi Daerah Irigasi Sanrego Kecamatan Kahu Kabupaten Bone Provinsi Sulawesi Selatan - Abdul Rivai Suleman (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2015)
Sanrego river located in the village Sanrego, District Kahu, Bone regency, South Sulawesi Province. This river has an important role to people's lives. In addition to functioning whether as a container supporting agriculture as well as one of the tourist place. But lately, frequently flooding during the rainy season. This happens due to a buildup of sediment in the irrigation channels at certain points. Namely on the primary channel, secondary channel, and tertiary. It has an impact on the performance of waterworks itself. This research aims to determine the amount of sediment (sediment-rate) that occurs on the channel point to review and to provide an overview and explanation of the value of the correlation coefficient (R) is based on the relationship between sediment discharge (QS) with water discharge (QW). This Research conducted by measuring directly on location by measuring the water level in each cross section of the channel and water sampling to test concentrations in the sediment. The results of research showed that the rate of sediment on the Primary Channel of Sanrego was 4,253 kg/day, Secondary Channel of Batu-Batu was 0,0593 kg/day, Tertiary Channel of Palakka 1 was 0,0403 kg/day, Palakka Tertiary Channel 2 is 0,0155 kg/day, Tertiary Channel of Batu-Batu 1 was 0,000578 kg/day, Tertiary Channel of Batu-Batu 2 was 0,0199 kg/day, with an average correlation coefficient (R) of 0,960, it shows the relationship between sediment discharge (QS) with water discharge (QW) has a positive direct perfect connection, which is between 0,6 < R <1,0. While on the secondary channel Palakka of 1,218 kg/day, with a correlation coefficient (R) of 0,210, this shows the relationship of sediment discharge (QS) and water discharge (QW) has a direct positive relationship is weak, that is between 0 < R < 0,6.